Tightlacing and Abusive Normative Address - Alexander Edlich; Alfred Archer (Ergo, An Open Access Journal of Philosophy)
In this paper, we introduce a distinctive kind of psychological abuse we call Tightlacing. We begin by presenting four examples and argue that there is a distinctive form of abuse in these examples that cannot be captured by our existing moral categories. We then outline our diagnosis of this distinctive form of abuse. Tightlacing consists in inducing a mistaken self-conception in others that licenses overburdening demands on them such that victims apply those demands to themselves. We discuss typical Tightlacing strategies and argue that Tightlacing typically is manipulative. Typical tightlacers will be motivated by a strong desire to suppress a kind of behaviour on the victim’s part. We will then differentiate Tightlacing from a related and widely discussed form of psychological abuse, Gaslighting. While Gaslighting focuses on the victim’s epistemic capacities and typically serves to insulate the abuser from potential dissent, Tightlacing focuses on the kind of person the victim is and typically serves to insulate the abuser from confronting ways of behaviour they cannot cope with. While Gaslighting targets the victim’s epistemic self-trust, Tightlacing targets their basic sense of who they are and their sense of entitlement to conduct themselves as who they really are. We finish by diagnosing the wrong-making features of Tightlacing, arguing that Tightlacing, among many secondary wrongs, makes the victim complicit in a denial of their rights as well as an erasure of who they are.